DIAGNOSTICS OF ULTRA-SLOW OMEGA POTENTIALS IN ADOLESCENT SCHOOLCHILDREN WITH ADAPTATION DISORDERS - Arzibekov , Абдикадир; Arzikulov, Абдурайим (International Journal of Scientific Pediatrics, 2023)
Abstract: One of the methods recommended for assessing the adaptation stress of children in connection with adaptation disorders is the non-invasive method of omegametry, which allows for a mass rapid assessment of the state of adaptation potentials. The purpose of the study was to establish a connection between disturbances between indicators of omega potentials depending on the mechanisms of adaptation and resistance of the child’s body. Material and methods: the study of SMFP in children was carried out depending on the severity of the degree of resistance of the children’s body (n=157; among them children with low body resistance (LRO) n=89, with very low resistance (VLO) n=58). Results: Comparing the indicators between healthy (30±1.8 mV) and children with very low body resistance, taking into account the intensity of the adaptation mechanisms, it was found that the more pronounced the failure of the adaptation mechanism, the lower the omega potential indicator (9.89 ± 0.76 mV ).